Opening doors understanding college reading - Cortina, Joe (McGraw-Hill, 2002)
[This book] is designed to help college students move from a pre-college reading level to a college reading level. It also presents a systematic way of approaching college textbook material that can make students more efficient in the study skills integral to their college success. While the scope of this book is broad, the focus is ultimately on comprehension. Comprehension skills are introduced early in the text and are integrated throughout subsequent chapters so that students learn how to apply them.-To the instructor.